Slow Sailing - Zupan, Uroš (knjige, 2022)
Uroš Zupan (1963) is one of Slovenia’s most prominent contemporary poets and he has made his mark on Slovenian poetry of the past 30 years. Slow Sailing presents the author’s own selection of the best of his best. This collection, which covers a period of more than two dozen years, is both personal and stern, since the author deals with his own poetry. From his delving into the golden age of his individual past to a sensuous hymn to soft summer light and the miracle of life that does not exist without the arts, Slow Sailing invites us to discover and re-discover one of post-independence Slovenia’s most distinctive poetic voices, while also offering a unique insight into Slovenian poetry at the turn of the millennium.The greatest Slovenian poet of the middle generation, his work has not been translated much (and not at all into English); the book is already part of the Slovenian canon and contains Zupan’s own selection of his finest poems. He is already included in school literature curricula.